Platelets in Neurodegenerative Conditions—Friend or Foe? - Leiter, Odette; Walker, Tara L. (Frontiers in Immunology, 2020)
It is now apparent that platelet function is more diverse than originally thought, shifting the view of platelets from blood cells involved in hemostasis and wound healing to major contributors to numerous regulatory processes across different tissues. With their intriguing ability to store, produce and release distinct subsets of bioactive molecules, including intercellular signaling molecules and neurotransmitters, platelets may play an important role in orchestrating healthy brain function. Conversely, a number of neurodegenerative conditions have recently been associated with platelet dysfunction, further highlighting the tissue-independent role of these cells. In this review we summarize the requirements for platelet-neural cell communication with a focus on neurodegenerative diseases, and discuss the therapeutic potential of healthy platelets and their released proteins to counteract these conditions.